Неравноправие граждан: новая политика в сфере здравоохранения Польши - Уотсон, П. (Социология: теория, методы, маркетинг, 2007)
The author discusses community health care in Poland nowadays. Since health care reforms were introduced in 1999, this sector of the country's economy has been the subject of criticism, dissatisfaction, and social protest. One of the striking aspects of the transition to capitalist democracy after communism is the extent to which healthcare reforms have met with lack of success. An important strand in the literature on the health policy analysis underlines the inseparability of policy and political context. The question for the analysis then becomes to what extent and how have health care reforms (along with other contextual changes) been producing the particular social transformations that have been experienced in Poland, and how has the changing national and transnational social order in turn, produced specific health reforms and outcomes there.